Five-year trends in maternal cardiac arrest in Maryland: 2013-2017. (3rd August 2022) - Lankford, Allison; Chow, Jonathan; Hendrickson, Eric; Jung, Myung Sun; Kodali, Bhavani; Malinow, Andrew; Goetzinger, Katherine; Mazzeffi, Michael
Abstract: Background: The United States (US) maternal mortality rate (MMR) continues to increase. Until recently, the MMR in Maryland (MD) was consistently higher than the national average. Maternal cardiac arrest (MCA) is a rare condition, but can lead to devastating consequences. The incidence of MCA in the US is approximately 6-8 per 100, 000 deliveries. To our knowledge there is no contemporary review of MCA in MD. Our primary aim was to determine the incidence of MCA in MD over a 5-year period. Secondary aims were to explore the causes of MCA, as well as characterize maternal and fetal survival. Materials and Methods: Maternal cardiac arrests in Maryland were identified using diagnostic codes and a statewide administrative database for the fiscal years 2013 through 2017. MCA incidence and mortality rates were compared with previously reported national data from 1998 to 2011. Demographic characteristics, medical co-morbidities, obstetric complications, mode of delivery, and fetal outcomes were collected for all patients. The apparent cause of MCA was determined for each patient. Complications and procedures performed in MCAs were also recorded. Results: In MD, 36 of 47 acute care hospitals provided maternity care. There were 32 cases of MCA in 332, 483 deliveries, an estimated incidence rate of 10 per 100, 000 deliveries (95% CI = 5–18). The most common apparent cause of MCA was hemorrhage. Maternal survival was 59.4%, while fetal survival was 93.8%. No significant differences were observed in MCA by age group. The incidence of MCA was significantly higher among non-Caucasian patients (24/177, 727) when compared to Caucasian patients (8/154, 732)( p =.01). Discussion: Maternal cardiac arrest in Maryland appears to be comparable to the US average, with similar maternal survival rates. Non-Caucasian patients appear to have a disproportionately high rate of these complications. While maternal mortality is high for MCA, fetal survival is excellent. Continued efforts and attention are needed to prevent MCA in underserved minorities and treat postpartum hemorrhage, the leading contributor to MCA over the past decade.